Empowering community on utilizing purun as liquid organic fertilizer in Tuwung Village Pulang Pisau Regency - Siti Unvaresi Misonia Beladona; Remi Ayu Pratika; Septaria Yolan Kalalinggi; Riandy Putra; Meiyanti Ratna Kumalasari (Universitas Muhammadiyah Malang, 2025)
Community service is crucial in addressing local challenges and empowering communities through knowledge and practical solutions. Tuwung Village, located in Kahayan Tengah Subdistrict, Pulang Pisau Regency, Central Kalimantan, includes 1,297 hectares of village forest within a convertible production forest area. With a population of 727 people, most of whom work in the agricultural sector, the community faces challenges related to using environmentally harmful chemical fertilizers. Despite the village's rich biodiversity, applying liquid organic fertilizers remains uncommon. Purun plants, a local resource, serve as a promising raw material for liquid organic fertilizer production due to their nutrient-rich composition, which benefits sustainable agriculture. This program focused on training the Tuwung community in utilizing purun as a raw material for liquid organic fertilizer to improve agricultural productivity while reducing dependence on environmentally damaging chemical fertilizers. Evaluation through pre- and post-tests demonstrated significant increases in participants' knowledge, skills, and interest in sustainable agricultural practices, with 88% of participants expressing a strong interest in using pure-based liquid organic fertilizer in the future. The program aligns with the United Nations' Sustainable Development Goals (SDGs), particularly Goal 2 (Zero Hunger) and Goal 12 (Responsible Consumption and Production), by promoting sustainable farming practices and encouraging the responsible use of local resources.